The Impact of SFAS 133 on Income Smoothing by Banks through Loan Loss Provisions - RANASINGHE, Tharindra (Institutional Knowledge at Singapore Management University, 2012)
We examine the impact of SFAS 133, Accounting for Derivative Instruments and Hedging Activities, on the reporting behavior of commercial banks and the informativeness of their financial statements. We argue that, because mandatory recognition of hedge ineffectiveness under SFAS 133 reduced banks’ ability to smooth income through derivatives, banks that are more affected by SFAS 133 rely more on loan loss provisions to smooth income. We find evidence consistent with this argument. We also find that the increased reliance on loan loss provisions for smoothing income has impaired the informativeness of loan loss provisions for future loan defaults and bank stock returns.